A Holistic Mission Approach: A Case Study of Missionary John Van NesteTalmage - Jeong, Moo-jin (International Journal of Psychosocial Rehabilitation, 2024)
Ever since its inception, Christianity has carried out evangelical ministry under the name of missionary work. Countless Christian denominations rushed into missionary work, knowing that they deserved to do so. In the process, inefficient and impersonal methods of missionary work were frequently used. Among them was the method of cultural imperialism that ignored the culture or character of the native people and reinforced the subjective way of life of missionaries. This is not a healthy mission work. Mission should be done in a holistic way: respecting the character of the native people, understanding their culture, and delivering the gospel in a good healthy way. A health index of a person may be described healthy when he or she is in harmony with spiritual, mental, and physical health. The present study attempts to set an example for healthy missionary work by examining and explaining the past ministry of a missionary who exemplified this holistic and healthy mission approach